Homer Hickam’s Journey as a Modern Hero: A Campbellian Analysis of the Movie October Sky - Dharejo, Nasrullah; Hingoro, Ahmed Ali; Dayo, Fatima (Annals of Human and Social Sciences, 2024)
This paper examines October Sky (1999), directed by Joe Johnston, through the lens of Joseph Campbell’s Hero’s Journey, analyzing Homer Hickam’s evolution from a coal miner’s son to a NASA engineer. Based on Hickam’s memoir Rocket Boys, the film highlights his pursuit of rocketry against societal and familial expectations. His journey reflects Campbell’s archetypal stages, including the call to adventure, atonement with the father, and the return with the elixir. A qualitative analysis mapped Homer’s experiences to Campbell’s Hero’s Journey framework. The study explored mentorship, conflict, and community influence on his development. Key figures such as Miss Riley and Homer’s father play significant roles. Homer’s progression aligns with the Hero’s Journey, underscoring themes of perseverance, education, and societal contribution. His success at NASA symbolizes individual and collective growth. Future research should analyze biographical films to explore how mentorship, resilience, and societal support drive personal transformation, addressing disparities in access to educational opportunities.